CTNI-50. A RANDOMIZED PHASE 2 TRIAL OF CEDIRANIB/OLAPARIB VERSUS BEVACIZUMAB IN PATIENTS WITH RECURRENT GLIOBLASTOMA: UPDATED RESULTS. (14th November 2022) - Hsieh, Annie; Gerstner, Elizabeth; Sahebjam, Solmaz; Piccioni, David; Campian, Jian; Drappatz, Jan; Aiken, Robert; Lee, Eudocia; Welch, Mary; Becker, Kevin; Williams, Mickey; Karlovich, Christopher; et al.
Abstract: PURPOSE: Hypoxia from inhibition of angiogenesis reduces DNA repair capacity. Targeting homologous recombination pathway also has anti-angiogenic effects. To examine the synergistic effects of disrupting DNA repair pathways and angiogenesis in glioblastoma, we combine cediranib (ced), a pan vascular endothelial growth factor (VEGF) receptor inhibitor with olaparib (ola), a poly-ADP ribose polymerase (PARP) inhibitor compared with bevacizumab (bev), a VEGF-A inhibitor alone. To identify potential biomarkers predicting response to treatments, we also perform whole exome sequencing on archival tissues. METHODS: Bevacizumab-naïve adult patients with first or second recurrence of glioblastoma after radiation and temozolomide were randomly assigned to cediranib (30mg PO daily)/olaparib (200mg PO twice daily) or bevacizumab (10mg/kg IV every 2 weeks). The primary end point was progression-free survival (PFS) at 6 months. The secondary end points included safety and overall survival (OS). Whole exome sequencing of formalin-fixed paraffin embedded archival tissue from 23 patients was performed. RESULTS: We are presenting the final data from this trial. Between December 2017 and November 2018, a total 70 adult patients with recurrent glioblastoma were randomly assigned to receive ced/ola (n = 35) or bev (n = 35). With a data cut off on 5/30/2022, median PFS was 118 days and 92 days in ced/ola and bev groups, respectively (hazard ratio, 1.099, 95% CI 0.6-2, p = 0.76). Median overall survival was 269.5 days and 192 days in ced/ola and bev groups, respectively (hazard ratio, 0.6892, 95% CI 0.39-1.2, p = 0.2). Whole exome sequencing was performed in total 23 patients (24 samples), 14 patients in the ced/ola group and 9 patients in the bev group. CONCLUSION: No significant survival benefit was observed in patients with recurrent glioblastoma treated with ced/ola compared to patients treated with bev monotherapy. Potential biomarkers predicting response to treatment identified from the whole exome sequencing on archival tissues will be presented.